Benthic foraminiferal stable oxygen isotope ratios (δ¹⁸O) at IODP Site 383-U1540 during Marine Isotope Stage 11 - Jebasinski, Lena; Frick, Daniel A; Kapuge, Aruggoda K I U; Basak, Chandranath; Saavedra-Pellitero, Mariem; Winckler, Gisela; Lamy, Frank; Gottschalk, Julia (In: Jebasinski, L et al. (2025): Stable oxygen isotope and trace element ratios, neodymium isotope composition, sedimentary census counts and opal content at IODP Site 383-U1540 during Marine Isotope Stage 11 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974158, 2025)
This dataset presents stable oxygen isotope ratios measured on the epibenthic foraminifera Cibicidoides wuellerstorfi and Cibicides kullenbergi at International Ocean Discovery Program Site U1540 (55° 8.47ʹ S, 114° 50.52ʹ W, 3580 m) during Marine Isotope Stage 11. Full replicates were conducted to determine the 1σ-uncertainty of the analyses. The results are expressed in delta-notation (δ¹⁸O) with reference to the Vienna Pee Dee Belemnite (VPDB) standard and were corrected by +0.64 ‰ VPDB to account for disequilibrium effects. The samples were measured with a Thermo Fisher Scientific MAT 253 isotope ratio mass spectrometer coupled to a Kiel IV carbonate preparation device at the Leibniz Laboratory for Radiometric Dating and Stable Isotope Research at Kiel University (Kiel, Germany).
Keywords: Bottom water oxygen; Bottom water temperature; Circumpolar deep water; Foraminiferal geochemistry; South Pacific Ocean